2012
DOI: 10.1246/cl.2012.585
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Separable CuFe2O4 Nanoparticle Catalyzed C–Se Cross Coupling in Reusable PEG Medium

Abstract: Unsymmetrical diaryl selenides (III) are obtained on arylation of phenylselenyl bromide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The crude product was purified by preparative TLC on silica gel (eluent: hexane/EtOAc). Details about compounds 3ab [30], 3ac [14], 3ad [17], 3ba [17], 3bb [31], 3ca [17], 3da [32], 3ea [28] and 3dc [30] were reported in the corresponding articles.…”
Section: Methodsmentioning
confidence: 99%
“…The crude product was purified by preparative TLC on silica gel (eluent: hexane/EtOAc). Details about compounds 3ab [30], 3ac [14], 3ad [17], 3ba [17], 3bb [31], 3ca [17], 3da [32], 3ea [28] and 3dc [30] were reported in the corresponding articles.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, the same investigators reported another method for the synthesis of diaryl selenides through the CuFe 2 O 4 ‐catalyzed CSe cross‐coupling of boronic acids with phenylselenyl halides in PEG‐400 medium (Scheme ) 195. Reaction of (hetero)arylboronic acids with phenylselenyl bromide produces the corresponding diaryl selenides in good to excellent yields within 8 h at 80 °C if CuFe 2 O 4 (5 mol %) is used as the catalyst in the presence of Cs 2 CO 3 as the base.…”
Section: Cx Bond‐forming Reactionsmentioning
confidence: 99%
“…In 2012, the same investigators reported another method for the synthesis of diaryl selenidest hrough the CuFe 2 O 4 -catalyzed CÀSe cross-coupling of boronic acids with phenylselenyl halides in PEG-400 medium (Scheme 153). [195] Reaction of (hetero)arylboronic acids with phenylselenyl bromide produces the corresponding diaryl selenides in good to excellent yields within 8h at 80 8Ci fC uFe 2 O 4 (5 mol %) is used as the catalyst in the presence of Cs 2 CO 3 as the base. Electron-donating substituents on the arylboronic acid improvet he yield of the reaction.…”
Section: Càse Coupling Reactionmentioning
confidence: 99%